DESIGN AND BUILD UP THE STIRRER VISCOMETER - Lamria Sri Manurung; Hendar Sudrajad (Jurnal Geliga Sains: Jurnal Pendidikan Fisika, 2018)
Fluids are substances that can flow. One of the flow substances is liquid. Every liquid has a characteristic that distinguishes a liquid from another liquid. One characteristic of a liquid is viscosity (thickness). The measuring instrument used to determine the viscosity of a liquid is a viscometer. Due to the importance of the amount of viscosity, so it is necessary to know the measurement easily, cheaply, and thoroughly. One method is to use a stirrer viscometer as a liquid viscous measurement devices. The purpose of this research was to determine the construction and test the designed stirrer viscometer. The research method used is the experimental method. The procedure of this research includes designing, assembling, and testing a stirring viscometer. The results of experiments that have been carried out show that the stirrer viscometer devices can to used to measure the viscosity of liquids with time and temperature indicators. This tool effectively proves that the temperature affects the viscosity of a liquid where the higher the temperature of the liquid, the lower the value of the viscosity of the liquid, and conversely the lower the temperature of the liquid, the higher the viscosity value of the liquid.